The Affordances and Constraints of Special Education Initial Teacher Licensure Policy for Teacher Preparation. (February 2017) - Blanton, Linda P.; Boveda, Mildred; Munoz, Lorena R.; Pugach, Marleen C.
Initial licensure polices in special education were examined to determine how these policies support or hinder reform efforts to develop teacher education programs that prepare graduates for the increasingly complex needs of diverse students. Initial special education licensure policies are described with an emphasis on the differences across states on two key options: whether licensure for special education teachers is a stand-alone initial license or whether the state requires a general education license prior to obtaining a second license in special education. As the field grapples with how best to prepare both general and special education teachers who can teach to high standards for students with disabilities, the influence of these options is examined in relation to four contemporary issues facing special education and the trade-offs that accrue when a particular licensure option is adopted.